Co-digestion of Wastewater-Grown Filamentous Algae With Sewage Sludge Improves Biomethane Production and Energy Balance Compared to Thermal, Chemical, or Thermochemical Pretreatments - Bohutskyi, Pavlo; Keller, Troy A.; Phan, Duc; Parris, Markeshia L.; Li, Mengyuan; Richardson, Lakesha; Kopachevsky, Anatoliy M. (Frontiers in Energy Research, 2019)
Wastewater algal treatment systems show improved economic viability and enhanced energy return on investment if integrated with biofuel production. One option is to anaerobically digest the algae to generate bio-methane. This method is appropriate for relatively low lipid filamentous algae typical of turf scrubbers®. However, an unbalanced algal biomass composition (e.g. carbon-to-nitrogen ratio, C/N) and the resistance of algae to biodegradation can limit biomass conversion into bio-methane. To evaluate options to enhance bio-methane production, an indigenous assembly of macro-algae was established and cultivated in CO2-infused secondary wastewater effluent, then harvested and either anaerobically digested using pretreatments or co-digested with sewage sludge. Results were used to develop methane production kinetic models and perform an anaerobic digestion (AD) system energy balance analysis to assess the feasibility of pretreatment and co-digestion for a scaled process. Floways were dominated by Ulothrix and Oedogonium algae and had periphyton biomass production rates that averaged 3.7 ± 0.4 g VS m−2 d−1 (±1 SD) during the initial 7-day colonization period. Biomass increased by 62% in the second half of the 14-day experiment. Ultimate methane yield from harvested biomass was improved relative to controls (306 ± 13 mL gVS−1) through thermal pretreatment by 15%, dilute acid by 5%, dilute alkali by 17%, and acid- and alkali-assisted thermochemical pretreatments by 23 and 27%, respectively. However, all pretreatment methods undermined the energy balance parameters including Net Energy Ratio (NER) and Net Energy Efficiency (NEE) due to the heat required for thermal pretreatments and the electricity needed to produce chemical reagents. In contrast, co-digestion of algal biomass with sewage sludge synergistically enhanced methane generation, yielding up to 401±3 mL gVS−1 at an algae-to-sludge ratio of 20% to 80%. Co-digestion with sludge also strongly improved AD system energy balance. NER and NEE increased from 2.8 and 73% for algae alone to 4.3 and 81% for a 20% to 80% algae-to-sludge mix, respectively. Moreover, the Net Energy Recovery during co-digestion reached 39% compared to 26 and 33% when algae or sewage sludge were processed as single-substrates. Thus, co-digestion of algae with sewage sludge serves as an attractive option for maximizing energy gain from AD of biomass harvested from filamentous algal treatment systems.